PENGUKURAN KINERJA PERUSAHAAN KOPI BUBUK “SAHABAT” DI LUBUKLINGGAU: APLIKASI BALANCED SCORECARD (BSC) - Aspriyati, Wiwik; Andani, Apri; Sukiyono, Ketut (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2017)
The purpose of this research is firstly to measure the company performance of Ground Coffee Sahabat viewed from the perspective of finance, customers, internal business processes, learning and growth. Second to recommend strategies that should be applied in the future. The method used is Balanced Scorecard (BSC), by measuring equally financially and non-financially, divided into four perspectives: financial, customer, internal business processes, learning and growth. The results showed that the company performance of Ground Coffee Sahabat based on financial perspective is good with the number of score 4, the perspective of the customer category good with the number of score 1, internal business process perspective in the category of good with a score of 5, and learning and growth perspective also in good category with score 1. Overall the performance of this company can be said good with the overall weighting value of 0.7 and is on the scale of business